Investigation of the Relationship Between the Nurses Organizational Citizenship Levels and Psychological Well-Being - Seda Yılmaz; Merve Kızılırmak Tatu (Association of Nurse Managers, 2023)
Aim: In this study, it was aimed to examine the relationship between nurses' organizational citizenship levels and their psychological well-being. Method: This descriptive study was conducted in a state hospital between. The sample of the study consisted of 146 nurses. The data of the study were collected using the 'Personal Information Form', the 'Organizational Citizenship Level Scale', and the 'Psychological Well-Being Scale'. Results: The mean age of the nurses is 36.19 (SD=7.19). 89% of the nurses are women, 79.5% are married, 76% have a bachelor's degree and 69.2% are living in the province where they live the longest, 85.6% have medium economic status, 36.3% It was determined that the working period was >15 years and 30.1% worked in other services. While the mean score of the Nurses' Organizational Citizenship Level Scale was found to be 3.97 (min.=2.3; max=4.9); The mean score of the Psychological Well-Being Scale was found to be 31.56 (min.=16; max=40). It has been determined that those with undergraduate and graduate degrees, those living in the city where they live the longest, and those working in the operating room have higher conscientiousness sub-dimension averages of the Organizational Citizenship Level Scale, and those with a total working time >15 years have higher helping sub-dimension averages. It was found that the mean scores of the Organizational Citizenship Level Scale tolerance and praising the institution sub-dimensions were higher in those working in the emergency department. Conclusion: A positive, weakly significant relationship was found between psychological well-being and organizational citizenship level (p<0.05). As the level of organizational citizenship increases, psychological well-being increases.